2017
DOI: 10.1155/2017/1069718
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Peroxisome Proliferator-Activated Receptors Using Thiazolidinediones: Strategy for Design of Novel Antidiabetic Drugs

Abstract: Thiazolidinediones are a class of well-established antidiabetic drugs, also named as glitazones. Thiazolidinedione structure has been an important structural domain of research, involving design and development of new drugs for the treatment of type 2 diabetes. Extensive research on the mechanism of action and the structural requirements has revealed that the intended antidiabetic activity in type 2 diabetes is due to their agonistic effect on peroxisome proliferator-activated receptor (PPAR) belonging to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 114 publications
1
49
0
2
Order By: Relevance
“…PPARγ is a nuclear receptor that acts as a transcription factor upon activation, by regulating the transcription and expression of specific genes encoding proteins involved in insulin signalling and gluco‐lipid metabolism. PPARγ is highly expressed in adipose tissue, skeletal muscle, liver, pancreatic β‐cells, heart, colon, placenta and in the cells of vascular and immune systems and plays critical roles in regulating insulin sensitivity, gluco‐lipid metabolism and adipogenesis . In the current study, we have shown overexpression of PPARγ notably increased the levels of NO, eNOS, p‐AKT, IκBα and the interaction of PPARγ and NFκB‐P65, and decreased the levels of ET‐1, p‐IKKα/β, TNFα, IL‐6, sICAM‐1 and sVCAM‐1.…”
Section: Discussionsupporting
confidence: 52%
“…PPARγ is a nuclear receptor that acts as a transcription factor upon activation, by regulating the transcription and expression of specific genes encoding proteins involved in insulin signalling and gluco‐lipid metabolism. PPARγ is highly expressed in adipose tissue, skeletal muscle, liver, pancreatic β‐cells, heart, colon, placenta and in the cells of vascular and immune systems and plays critical roles in regulating insulin sensitivity, gluco‐lipid metabolism and adipogenesis . In the current study, we have shown overexpression of PPARγ notably increased the levels of NO, eNOS, p‐AKT, IκBα and the interaction of PPARγ and NFκB‐P65, and decreased the levels of ET‐1, p‐IKKα/β, TNFα, IL‐6, sICAM‐1 and sVCAM‐1.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, promising clinical results about the PPARγ belongs to a nuclear hormone receptor superfamily of ligand-inducible transcription factors that heterodimerize with the retinoid X receptor (RXR) [108] and bind to peroxisome proliferator response elements (PPREs) in the promoter region of target genes [109]. Although present in most cell types, such as vessels, neurons, macrophages, microglia and astrocytes, in which it attenuates the expression of proinflammatory mediators [110], PPARγ is predominantly expressed in adipocytes, wherein modulates lipid metabolism in form of release, transport, and storage of free fatty acids (FFAs) [111,112]. By enhancing the uptake and storage of FFAs in adipose tissue, PPARγ agonists may decrease ectopic fat accumulation [113], thus preserving non-adipose peripheral tissues from the wide range of lipotoxicity complications, including IR, liver steatosis, hyperglycemia and CVD [114].…”
Section: Meddiet and Purple Plant-derived Anthocyanin Extracts For Nementioning
confidence: 99%
“…Among these treatments, sulfonylureas improve insulin secretion by the regulation of the ATP-sensitive potassium channels in the plasma membrane of pancreatic β-cells [ 7 ]. Thiazolidinediones, agonists of nuclear peroxisome proliferator-activated receptor gamma (PPARγ), increase insulin sensitivity in liver and skeletal muscle [ 8 ]. Glinides stimulate insulin secretion rapidly and for a short period when needed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%